Clinical Effectiveness of Prophylactic Zinc on Growth, Pneumonia and Diarrhea in Children Less than 1 Year - Batool, Naima; Shaikh, Salma; Chohan, Muhammad Nadeem (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To assess the impact of prophylactic Zinc supplementation in children on growth parameters (weight, length and, OFC) and the reduction of frequency of Diarrhea and Pneumonia. Methodology: This Randomized Control Trial was done at EPI center in Outpatient department at Liaquat University Hospital, Hyderabad from April-November 2015. In this study, we randomly assigned 263 children aged 6 weeks to 1 year to receive either zinc or a placebo suspension orally during 5 months follow up visits. There were three refusals and 22 dropped out cases during the study. A total of 134 children received zinc and 129 received placebo. Data were analyzed and compared between two groups by calculating Mean and Standard Deviation of age, weight, length percentages of gender, frequency and percentages of diarrhea and pneumonia number of visits, episodes of fever. RESULTS: The average percentage of ALRI was 8.9% in Zinc and 11.4% in Placebo group. Placebo group had high percentage of diarrhea for > 4 days than Zinc group in children. Placebo group had high percentage of Respiratory Infection for > 5 days than Zinc group in children. Placebo group had high percentage in Diarrheal episodes ? 3 in a month than Zinc group children. Both groups had same growth of length during Follow up visits. OFC development in both groups had not much difference. Both groups started earlier complimentary feeding with no big difference. CONCLUSIONS: Prophylactic zinc supplementation had influence on growth parameters in children from six weeks to one year and showed decreased frequency of Diarrhea and Pneumonia. KEY WORDS: Infants, Micronutrients, infections, Growth, Zinc